Effect of ultraviolet light treatment on surface hydrophilicity and human gingival fibroblast response on nanostructured titanium surfaces - Areid N; Peltola A; Kangasniemi I; Ballo A; Närhi TO (WILEY, 2022)
This study was designed to investigate the effect of nanostructured TiO2 coatings on human gingival fibroblast and to explore the influence of ultraviolet (UV) light on surface wettability and cellular response. Ti-6Al-4V titanium alloy discs (n=96) were divided into three groups: a sol-gel-derived MetAlive (MA) coating; hydrothermal (HT) coating; and a non-coated (NC) group. Forty-eight titanium substrates were further treated with UV light for 15min. The water contact angles of the substrates were measured using the sessile drop method. Human gingival fibroblasts were used to evaluate the cell adhesion strength and cell proliferation on experimental surfaces. The strength of cell adhesion against enzymatic detachment was studied after 6hr of adhesion using gentle trypsinization for 15min at room temperature. A fluorescence microscope was used for cell imaging (Zeiss-stereo-lumar-v12), and images were analyzed for cell counting, and the percentage of detached cells were calculated. The proliferation of cultured cells up to 10days was determined according to the cell activity using Alamar Blueassay. The HT group had the lowest contact angle value (31.1 degrees) followed by MetAlive (35.3 degrees), whereas the NC group had the highest contact angle (50.3 degrees). After UV light treatment, all surfaces become considerably more hydrophilic. There was a significant difference in the amount of adherent cells between sol-gel and HT groups when compared with the NC group (p<.05) with detachment percentages of 35.8%, 36.4%, and 70.7%, respectively. All substrate types showed an increase in cell proliferation rate until 10days. It can be concluded that nanostructured titanium oxide implant surfaces, obtained by sol-gel and HT coating methods, enhance the surface wettability and improve human gingival fibroblast function in terms of adhesion and proliferation rate when compared with non-coated surfaces. UV light treatment clearly enhances the wettability of all titanium surfaces.